2021
DOI: 10.31002/metathesis.v4i3.3195
|View full text |Cite
|
Sign up to set email alerts
|

EFL Teachers’ Challenges and Insights of Online Teaching amidst Global Pandemic

Abstract: <p class="AbstractText">The unexpected shift of English language teaching from face-to-face classroom interaction to online learning activities using digital platforms has resulted in a number of challenges for English teachers and students. Hence, examining the teachers’ challenges and their insights of the online learning activities is highly required. The present study sheds some light on university EFL teachers’ challenges and insights of online learning activities amidst global pandemic. Drawing on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 0 publications
5
59
1
4
Order By: Relevance
“…EFL teachers faced a challenge that they did not familiar with the use of online platform to conduct an online learning in remote learning context (Nugroho, Ilmiani, & Rekha, 2021). This is also by previous research, which states that one of the challenges of English in implementing mobile learning is the competence of teachers in operating technology (Rosalina, Nasrullah, & Elyani, 2020).…”
Section: Discussionmentioning
confidence: 87%
“…EFL teachers faced a challenge that they did not familiar with the use of online platform to conduct an online learning in remote learning context (Nugroho, Ilmiani, & Rekha, 2021). This is also by previous research, which states that one of the challenges of English in implementing mobile learning is the competence of teachers in operating technology (Rosalina, Nasrullah, & Elyani, 2020).…”
Section: Discussionmentioning
confidence: 87%
“…Correspondingly, this study revealed that teachers prepared learning materials and online assessments long days before their teaching schedule. This is supported by Nugroho and Mutiaraningrum (2020) and Nugroho, Ilmiani, and Rekha (2020) reporting that online learning consumes a lot of time to prepare the learning materials. Moreover, the unfamiliarity of using online learning platforms such as sending documents/files, creating tasks deadline, checking students' presence, submitting tasks, and archiving students' work becomes another great challenge for teachers in their online class (Sun et al, 2020).…”
Section: Discussionmentioning
confidence: 88%
“…This is in line with a study done by Salima (2012) who mentioned that students' deficiencies in writing skill are the result of their poor background knowledge of the target language, lack of practices and low motivation in writing. Poor background knowledge in target language might lead to students' difficulties in understanding the task (Nugroho et al, 2021). Furthermore, lack of practices and low motivation in writing caused the students to write irrelevant, unclear and repetitive information.…”
Section: Discussionmentioning
confidence: 99%